2022
DOI: 10.3390/molecules27217323
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Behavior of an Amide Functionalized Mn(II) Coordination Polymer on ORR, OER and HER

Abstract: The new 3D coordination polymer (CP) [Mn(L)(HCOO)]n (Mn-CP) [L = 4-(pyridin-4-ylcarbamoyl)benzoate] was synthesised via a hydrothermal reaction using the pyridyl amide functionalized benzoic acid HL. It was characterized by elemental, FT-IR spectroscopy, single-crystal and powder X-ray diffraction (PXRD) analyses. Its structural features were disclosed by single-crystal X-ray diffraction analysis, which revealed a 3D structure with the monoclinic space group P21/c. Its performance as an electrocatalyst for oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…28 In a prior study, we reported several CPs derived from amide-functionalized ligands that exhibited remarkable activity in C-C coupling reactions, dye adsorption, supercapacitors and electrocatalysts for the OER and overall water splitting. [29][30][31][32] Distinguished by well-defined structures and tunable properties, these materials present a promising avenue to address challenges associated with conventional catalysts. The intricate interplay between metal centers and organic ligands in CPs/MOFs yields tailored active sites that can enhance OER kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In a prior study, we reported several CPs derived from amide-functionalized ligands that exhibited remarkable activity in C-C coupling reactions, dye adsorption, supercapacitors and electrocatalysts for the OER and overall water splitting. [29][30][31][32] Distinguished by well-defined structures and tunable properties, these materials present a promising avenue to address challenges associated with conventional catalysts. The intricate interplay between metal centers and organic ligands in CPs/MOFs yields tailored active sites that can enhance OER kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we systematically changed the position of the pyridine nitrogen atom in amide-based ligands, creating CPs capable of catalysis, 29 dye adsorption, 30 water splitting, 31,32 and supercapacitance. 31 The present study presents a novel amide-based multifunctional proligand, 4-(pyrimidin-5-ylcarbamoyl)benzoic acid (HL, Scheme 1), with a pyridinium moiety.…”
Section: Introductionmentioning
confidence: 99%